2022
DOI: 10.5194/hess-26-4125-2022
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic offsets between bulk plant water and its sources are larger in cool and wet environments

Abstract: Abstract. Isotope-based approaches to study plant water sources rely on the assumption that root water uptake and within-plant water transport are non-fractionating processes. However, a growing number of studies have reported offsets between plant and source water stable isotope composition for a wide range of ecosystems. These isotopic offsets can result in the erroneous attribution of source water used by plants and potential overestimations of groundwater uptake by the vegetation. We conducted a global met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 164 publications
3
38
2
Order By: Relevance
“…This indicates that the CVD biases we observed on Larix may also be applicable to other taxa. The magnitude of the biases may be slightly different among species (Zhao et al, 2022;Chen et al, 2020;De La Casa et al, 2022), but the AWA-dependency of the biases should show consistency. We also want to highlight that the observed isotope fractionation likely depends on the setup (e.g.…”
Section: On the Processes Causing Isotope Fractionation During Cvd Ex...mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the CVD biases we observed on Larix may also be applicable to other taxa. The magnitude of the biases may be slightly different among species (Zhao et al, 2022;Chen et al, 2020;De La Casa et al, 2022), but the AWA-dependency of the biases should show consistency. We also want to highlight that the observed isotope fractionation likely depends on the setup (e.g.…”
Section: On the Processes Causing Isotope Fractionation During Cvd Ex...mentioning
confidence: 99%
“…Theoretically, about 30 % to 50 % of the H atoms of cellulose and its precursors are exchangeable (Schuler et al, 2022;Filot et al, 2006). If the CVD extraction disturbs the previously established isotopic equilibration between organic tissue and tissue water because of the gradually isotopically enriched tissue water during extraction, the potential H exchange would affect ecohydrological interpretations of 2 H (Barbeta et al, 2020;De La Casa et al, 2022). However, Chen et al (2020) were unable to isolate the H exchange that occurred during the extraction.…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption was challenged when multiple studies observed that the isotopic composition of xylem water does not always fall within the range of the isotopic composition of the source waters (Penna et al, 2018). Some studies hypothesised that physiological mechanisms at the soil-root interface (Poca et al, 2019), leaf-atmosphere scale (Cernusak et al, 2016) and along the flow of the sap within the xylem might cause a depletion in 2 H xylem water and consequently, a deviation from the uptake sources (de la Casa et al, 2022). Additionally, there is increasing evidence that water compartmentalisation between flowing and stored water can occur within the stem (Barbeta et al, 2022;Zhao et al, 2016) and that the daily withdrawal of water from storage cells might affect the xylem isotopic composition (Dubbert & Werner, 2018).…”
mentioning
confidence: 99%
“…It should be noted that isotopic spatial heterogeneity of xylem water induced by sampling position and time (Nehemy et al, 2022) and soil water induced by uneven distribution of throughfall and preferential flow (Xiang et al, 2019;Yang and Fu, 2017) could lead to an isotopic offset. Recently, isotopic offsets between plants and their potential water sources have also been found in various ecosystems, which may hinder the unambiguous identification of water sources and influence the accurate assessment of DLSW utilization (Barbeta et al, 2022;de La Casa et al, 2022;Zhao et al, 2016). Some studies argued that isotopic fractionation during root water uptake could be attributed to the existence of Casparian strips which can lead to isotope enrichment in root water and depletion in xylem water (Naseer et al, 2012;Vargas et al, 2017).…”
Section: Limitations Due To the Extraction Methodsmentioning
confidence: 99%
“…Orlowski et al (2016aOrlowski et al ( , b, 2018 suggested that the fractionation is mainly related to cryogenic vacuum distillation (CVD). However, the CVD is still the most common methodology for water extraction to date (De La Casa et al, 2022). Plant water use strategies in various ecosystems have been researched extensively using natural stable water isotopic techniques (Beyer et al, 2016;Dawson and Ehleringer, 1991;Jiang et al, 2020;Miguez-Macho and Fan, 2021).…”
Section: Introductionmentioning
confidence: 99%